Dari Toponimi Hingga Gastronomi: Melacak Tinggalan Jaringan Perdagangan Rempah di Banten - Eva Syarifah Wardah; Eneng Malihatunnajiah (Tsaqofah, 2022)
Banten as an emporium which has progressed quite rapidly, especially in the spice trade network. Based on historical records, Banten was the administrative center of the Banten Sultanate as well as the center of the spice route with the main commodity of pepper, which has the best quality in the archipelago. The smell of spices eventually made merchants from various countries, such as Arab, Persian, Gujarat, Indian, Chinese, Dutch, Portuguese, and English visit Banten. So that since the 16th century Banten was known as a pepper and another spices such as pepper, nutmeg, cloves, cardamom, ginger, turmeric, cinnamon and many more. The foreigners are coming to Banten, made the sultan issue a policy of open free trade politics, among others, organizing the area based on ethnicity, activities, and production. The sultan’s policy had a major influence on the tracking of the spice routes in Banten. Besides spices being the political and economic reason for the Banten Sultanate to prosper the people, spices are also a catalyst for Banten’s domination and competition with foreign nations. The traces of this spice route become the heritage of the ancestors who have the values ​​of local wisdom.